"IMPERATIVE DIVERSITY: JAPANESE AND INDONESIAN" (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on imperative sentences in Indonesian and Japanese that compare the diversity of forms and meanings contained in the imperative sentences of the two languages. This study aims to contrast the lingual elements found in Indonesian and Japanese, namely about imperative sentences or better known as command sentences. Thus from this research it is expected to be able to explain more deeply about imperative sentences that exist in both languages, and see what differences arise from each imperative context. This study uses a contrastive method in which the lingual elements of the two languages studied are contrasted and conclusions drawn to be used as additional scientific insights. The results of this study indicate that imperative sentences in Indonesian have various meanings and can be conveyed with other sentence constructions. Unlike the Japanese language which has its own peculiarities with a variety of imperative markers that it has.